MENINJAU EFEKTIVITAS KERANGKA HUKUM DALAM MENANGANI KEKERASAN TERHADAP ANAK DAN PEREMPUAN DI INDONESIA - Ade Arga Wahyudi (CV. Denasya Smart Publisher, 2024)
Violence against children and women in Indonesia is a serious problem that reflects weaknesses in the legal protection system. Various social factors such as poverty, low education, patriarchal culture, gender inequality, and early marriage exacerbate the situation. This phenomenon demands deep reforms in policy and law enforcement to ensure protection and justice for victims. This research aims to analyze the effectiveness of the legal protection system for children and women in Indonesia, highlighting policy gaps, structural barriers, and the impact on victims. The research uses a normative-empirical method with a descriptive-qualitative approach. Data was collected through a literature review of laws and regulations, as well as analysis of other legal and non-legal documents. The results identified eight main obstacles in law enforcement, including suboptimal implementation of additional punishment, stereotyping, victim blaming, revictimization, and difficulties in presenting evidence at trial. Punishments that are still oriented towards imprisoning perpetrators and the lack of understanding of power relations among legal officers add to the complexity of the problem. In addition, victims often do not report their cases due to lack of legal support and the risk of psychological impact is not considered. Legal reform is needed to create responsive and humane protection. Improve training of law enforcement officers, provide one-stop service centers for victims, expand public awareness campaigns, and increase budget allocations to support more effective policy implementation.